2020
DOI: 10.1038/s41420-020-00325-8
|View full text |Cite
|
Sign up to set email alerts
|

SerpinA3N deficiency deteriorates impairments of learning and memory in mice following hippocampal stab injury

Abstract: Traumatic brain injury is a global leading cause of disability and death, which puts patients at high risk for developing dementia. Early intervention is believed as the key to minimize the development of brain damages that could aggravate the symptoms. Here, we report that the serine protease inhibitor SerpinA3N is upregulated in hippocampal neurons in the early stage of hippocampal stab injury (HSI), while its deficiency causes a greater degree of neuronal apoptosis and severer impairments of spatial learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…Consistent with our microglial RNAseq data, this also did not co-localize with IBA1. Neurons and oligodendrocytes have both been demonstrated to upregulate Serpina3n expression in the setting of CNS injury, making it likely that these cell types account for the Serpina3n expression that did not co-localize with GFAP in our experiments [ 31 , 32 ]. Overall, the data obtained from our combined fluorescent in situ hybridization and immunofluorescence experiments validated the lineage-specific gene expression changes detected by RNAseq and provided information on the spatial distribution of the genes examined.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our microglial RNAseq data, this also did not co-localize with IBA1. Neurons and oligodendrocytes have both been demonstrated to upregulate Serpina3n expression in the setting of CNS injury, making it likely that these cell types account for the Serpina3n expression that did not co-localize with GFAP in our experiments [ 31 , 32 ]. Overall, the data obtained from our combined fluorescent in situ hybridization and immunofluorescence experiments validated the lineage-specific gene expression changes detected by RNAseq and provided information on the spatial distribution of the genes examined.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most robust differences observed in the NanoString panel was a serine protease inhibitor, SERPINA3N . Previous research has shown a role for SERPINA3N in neuroprotection, 47,48 with polymorphisms being associated independently with Alzheimer’s disease, 49 Parkinson’s disease, 50 and progressive multiple sclerosis. 51 SERPINA3N encodes α1-antichymotrypsin (ACT), acutely inhibits chymotrypsin and cathepsin G, serving as a modulator of inflammation and complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…Also in experimental TBI, high levels of expression of Serpina3n, an astroglial activation marker, are found in neurons in the early stage of the injury [ 9 ]. Meanwhile, it is observed in another study that the knockout of Serpina3n led to increased neuronal apoptosis in neurons, and that an MMP2-specific inhibitor might serve as a therapeutic target for neurotrauma [ 10 ]. In addition, Trem2 and Tyrobp have been identified as major regulators and therapeutic targets in TBI [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%